PERAN SEKOLAH DALAM PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS (MBG) DI UPTD SMP NEGERI 1 SIROMBU - Gulo, Nirawati; Hulu, Syukur Kasieli; Bawamenewi, Adrianus; Zendrato, Restu Yandika Sakti (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT The Free Nutritious Meal Program (MBG) is a national initiative launched by the government to improve the quality of human resources starting from school age, with schools serving as the primary implementers at the educational unit level. This study aims to analyze the implementation of the roles and functions of schools in the Free Nutritious Meal Program (MBG) at UPTD SMP Negeri 1 Sirombu. The research employed a descriptive approach with a qualitative method. Data were collected through observation, interviews, and documentation involving the principal, one teacher, and one student as informants. Data analysis was conducted through data reduction, data display, and interactive conclusion drawing, strengthened by source triangulation to ensure the validity of the findings. The results indicate that the school’s role has been implemented systematically, including identifying student beneficiaries such as those with special conditions providing supporting facilities, receiving and inspecting meals, distributing food, supervising consumption, and preparing accountability reports. The school’s functions in this program include ensuring accurate targeting, addressing students’ special needs, guaranteeing that meals are appropriate, safe, and nutritious, and creating an orderly and comfortable consumption process. Overall, the school’s active involvement in managing and supervising the program is a key factor in the successful implementation of MBG and demonstrates that optimizing managerial and supervisory functions significantly determines the program’s effectiveness at the school level. ABSTRAK Program Makan Bergizi Gratis (MBG) merupakan program nasional yang dicanangkan pemerintah untuk meningkatkan kualitas sumber daya manusia sejak usia sekolah, dengan sekolah sebagai pelaksana utama di tingkat satuan pendidikan. Penelitian ini bertujuan untuk menganalisis pelaksanaan peran dan fungsi sekolah dalam implementasi Program Makan Bergizi Gratis (MBG) di UPTD SMP Negeri 1 Sirombu. Penelitian menggunakan pendekatan deskriptif dengan metode kualitatif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dengan informan yang terdiri atas kepala sekolah, satu guru, dan satu siswa. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan secara interaktif, serta diperkuat dengan teknik triangulasi sumber untuk menjamin keabsahan temuan. Hasil penelitian menunjukkan bahwa pelaksanaan peran sekolah telah berjalan secara sistematis, meliputi pendataan peserta didik penerima manfaat termasuk yang memiliki kondisi khusus, penyediaan sarana pendukung, penerimaan dan pengecekan makanan, pendistribusian, pengawasan saat konsumsi, hingga penyusunan laporan pertanggungjawaban. Fungsi sekolah dalam program ini mencakup memastikan ketepatan sasaran, memperhatikan kebutuhan khusus peserta didik, menjamin makanan yang layak, aman, dan bergizi, serta menciptakan proses konsumsi yang tertib dan nyaman. Secara keseluruhan, keterlibatan aktif sekolah dalam pengelolaan dan pengawasan program menjadi faktor kunci keberhasilan implementasi MBG serta menunjukkan bahwa optimalisasi fungsi manajerial dan pengawasan sekolah sangat menentukan efektivitas program di tingkat satuan pendidikan.